Factors associated with institutional delivery practice among women in pastoral community of Dubti district, Afar region, Northeast Ethiopia: a community-based cross-sectional study - Wassie Sadik; Alemayehu Bayray; Ayal Debie; Tsegaye Gebremedhin (BMC, 2019)
Abstract Background Eighty-five percent of the global burden of maternal mortality was covered by Sub-Saharan Africa. Ethiopia is a major contributor to the death of mothers with a maternal mortality ratio of 676 per 100,000 live births. Only 10% of deliveries in Ethiopia were at health facility with the least (6.4%) in the Afar region. However, there is limited evidence about factors of institutional delivery in the study area. Thus, this study aimed to assess the magnitude and associated factors of institutional delivery practice among women in the pastoral community of Dubti district, Northeast Ethiopia. Methods A community based cross-sectional study was conducted from April to May 2016, in the pastoral community of Dubti district. A total of 381 women were selected using systematic sampling technique and interviewed using a standardized structured questionnaire. Binary logistic regression analysis was computed. In the final multivariable logistic regression analysis adjusted odds ratio (AOR) with 95% confidence interval (CI) was used to declare the factors associated with institutional delivery. Results This study revealed that 35.2% (95% CI: 30.5-40.1) of women were delivered at the health facility. Women who had travelled less than an hour to reach the nearest health facilities (AOR: 4.90, 95% CI: 2.62-9.18), attending antenatal care (AOR: 2.50, 95% CI:1.48-4.23), previous history of stillbirth (AOR: 4.34, 95% CI: 1.78-10.58), good knowledge (AOR: 2.09, 95% CI:1.23-3.56), and husband involved in decision making on delivery place (AOR: 4.42, 95% CI: 1.98-9.90) were the factors associated with institutional delivery practice. Conclusions The overall institutional delivery practices in the study area was low as compared to the national level. This low practice of institutional delivery was contributed by residing far from the facility, does not received antenatal care, and having low awareness about ANC follow up and institutional delivery services. Therefore, strengthening the accessibility of health facility to nearby mothers resided, antenatal care services, and awareness creation provision at the community level for pregnant women in the pastoral community can improve institutional delivery practice.